The simpsons a complete guide to our favorite family - Richmond, Ray (Harper collins publisher, 1997)
The Simpsons Complete Guide to your Favorite Show is a celebration of this family's phenomenal decade. Arranged by season, the book covers each episode of the television show.
Keywords: Comics & Graphic Novels; General; Media Tie-In Humor